Qualidade de vida das pessoas com doença falciforme do centro de referência do município de Feira de Santana - Bahia - Almeida, Candisse Alves de (2017)
The objective of this study was to analyze the quality of life (QoL) of people with sickle cell disease (DF) from the perspective of the social health determination model (MDSS). A scientific paper entitled "Quality of life of people with sickle cell disease and the model of social determination of health" was constructed. The study of the QoL assessment of people with DF is considered a tool to reach the social and scientific visibility of this illness in the national scenario. The study of the evaluation of QoL in chronic diseases, like DF, is extremely important, since the impact of the disease on QoL strongly influences the way the subject faces his illness. It was a challenging study that sought to understand QOL in people with FD as a phenomenon of great complexity, on which individual and collective conditions are linked, considering not only biological and hereditary conditions, but also social and cultural, capable of influencing the perception of the individual and determining their health condition and these characteristics illustrate the social determinants of health. In view of this complex scenario, we suggest the development of specific instruments to evaluate the QoL of people with FD, considering all the peculiarities inherent to this disease so prevalent in the northeastern territory